Education for social citizenship : perceptions of teachers in the USA, Australia, England, Russia and China - Lee, W. O., 1954-; Fouts, Jeffrey T. (Book collections on Project MUSE., 2005)
This volume, emerging from a cross-national study of teachers' perception of good citizenship, addresses two fundamental questions: What do teachers see as important in citizenship education? How do these perceptions facilitate or hinder the preparation of good citizens? While providing rich and useful data on the latest developments of citizenship education in various contexts, this book also offers an all-round review of concepts and arguments on the subject, as well as insightful comparative analyses of the findings emerged from the case studies. One encouraging conclusion drawn from these studies is that teachers across nations share similar goals and objectives that seem to have transcended cultural and political boundaries.